Two New Species of Hiptage Gaertn. (Malpighiaceae) from India - Srivastava, R. C. (Indian Forester, 1984)
Two new specIes of Hiptage Gaertn. viz. H. jacobsii Srivastava and H. nayarii Srivastava have been described and illustrated.